RETRACTED: Innovative foam materials for designing eco-friendly wetsuits - Zufarova Zulfiya; Tashpulatov Salikh; Tyurin Igor; Tairov Bakhtiyor; Holoqov Kurbonali (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001